Synthesis, fabrication and characterization of composite scaffolds employing sodium alginate, nanoclay and hydroxyapatite for articular cartilage tissue engineering - Padideh Shahbazi; Majid Abdouss; Mitra Naeimi; Goldis Darbemamieh; Milad Jafari-Nodoushan (Carbohydrate Polymer Technologies and Applications)
In this paper, composite scaffolds consisting of sodium alginate (SA), nanoclay (NC) and hydroxyapatite (HA) were fabricated for articular cartilage tissue engineering using freeze-drying method. Central composite design (CCD)-based response surface methodology (RSM) was used to anticipate the mechanical characteristics (in both compressive and tensile tests) and in vitro degradation of scaffolds with different amounts of SA and NC. The maximum tensile and compressive moduli (10.5 and 0.99 MPa, respectively) were found for the scaffold containing 2 g SA, 0.02 g NC and 0.2 g HA. In addition, it was found this composition had a relatively low degradation rate. Moreover, the optimized composition (S2N0.02) displayed a favorable porosity (50 %) and a proper swelling behavior. FTIR confirmed the successful integration of SA, NC and HA by presenting characteristic peaks corresponding to their functional groups, and SEM images showed the homogeneous dispersion of nanoparticles in the polymer matrix and the formation of interconnected pores suitable for cell seeding. Furthermore, MTT assay corroborated the good biocompatibility of the scaffolds for human chondrocytes. Drug release study showed that the scaffolds could effectively load glucosamine and provide its sustained release. These results confirm that SA/NC/HA composite scaffolds possess desirable properties for articular cartilage tissue engineering applications.